(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
This article presents a brief theoretical review of the literature on the issue of anxiety and its impact on the status of the student psychologist in the group. The results of the diagnostic study on the level of anxiety and status in the group are presented.